Successful management of a pediatric cardiac patient with Bombay blood group and leukocyte adhesion deficiency type II: A case report and literature review - Ahmad Abuzaid; Ahmed Abdalwahab (Saudi Journal of Anaesthesia, 2025)
Bombay blood group is a rare blood phenotype, frequently misinterpreted as “O” blood group, and sometime causes severe hemolytic transfusion reactions. We are reporting a 4-year-old cardiac patient with congenital heart disease. During routine intraoperative evaluation, the patient was confirmed as having Bombay blood group and leukocyte adhesion deficiency type II. As this condition is extremely rare in Saudi Arabia, matched blood donors were secured from outside the country. The patient underwent bilateral peripheral artery stenosis reconstruction. Successful intraoperative management was done using one unit of matched blood transfusion, acute normovolemic hemodilution strategy, intravenous injection of antifibrinolytic agents, and regular antimicrobial surgical prophylaxis. The postoperative period was uneventful, and the patient was discharged from the hospital 1 week later. Correct and preoperative identification of Bombay phenotype, patient labeling and flagging, maintaining records for rare blood groups, and collaborations with other blood banks are necessary strategies for safe management of patients with Bombay blood group.